Brazil Anticorpos anti-Brucella canis e anti-Brucella abortus em caes de Araguaina, Tocantins - Dorneles, Elaine Maria Seles (2011)
The aims of the present study were to determine the seroprevalence of infection by Brucella canis and Brucella abortus and to evaluate possible risk factors for infection in dogs from Araguaina, Tocantins, Brazil. Sera from 374 dogs, of the urban zones of the municipality, from both sexes, were submitted to the agar-gel immunodiffusion for Brucella canisantibodies and to rose Bengal test (AAT) and fluorescence polarization assay (FPA) for Brucella abortus-antibodies. From the 374 tested dogs, 21 reacted in the AAT, but no one was positive in the FPA. The seroprevalence of B. canis infection found in Araguaina, Tocantins, Brazil, was 44.53% (95% IC; 39.43 to 49.72). No association was found among seropositivity for B. canis and the risk factors studied. Thus, data from the present study showed that there was no infection by B. abortus among dogs in the sample and that infection by B. canis is widespread and at high prevalence in Araguaina, Tocantins, Brazil.